2021
DOI: 10.1021/acsanm.1c01819
|View full text |Cite
|
Sign up to set email alerts
|

Ni Nanoparticles Grown on SiO2 Supports Using a Carbon Interlayer Sacrificial Strategy for Chemoselective Hydrogenation of Nitrobenzene and m-Cresol

Abstract: To efficiently increase the dispersity of metal nanoparticles (NPs) of the supported-type catalyst is crucial for promoting their catalytic performance owing to the enlarged amount of exposed active sites and the strengthened metal–support interaction. Therefore, to develop a facile and practical method for preparing a supported-type catalyst with high dispersity is of great significance, but remains a challenge. In this work, inspired by the previously reported non-noble metal sacrificial approach, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…A broad range of applications was found for nickel nanoparticles (Ni NPs), which can be used in electrocatalysis, photocatalysis, or biomedicine [10,11]. These unique properties of NPs as catalysts derive from the large percentage of coordinatively unsaturated atoms located at the surface, edges, and corners of the NPs compared to the total number of atoms [12].…”
Section: Introductionmentioning
confidence: 99%
“…A broad range of applications was found for nickel nanoparticles (Ni NPs), which can be used in electrocatalysis, photocatalysis, or biomedicine [10,11]. These unique properties of NPs as catalysts derive from the large percentage of coordinatively unsaturated atoms located at the surface, edges, and corners of the NPs compared to the total number of atoms [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the high cost and scarcity of resources with noble metals limit their industrial applications. Transition metals, including Ni, Cu, , Fe, , and Co, are promising alternatives due to their abundant reserves, low cost, and good catalytic performance under certain conditions. For instance, 10%Ni/r–SiO 2 –CIS illustrated good catalytic activity for nitrobenzene hydrogenation under the reaction condition of 150 °C and 1.0 MPa of H 2 , while Ni@NCQDs achieved high activity (100%) and selectivity (99.8%) for the reduction of p -chloronitrobenzene to p -chloroaniline.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metals, including Ni, Cu, , Fe, , and Co, are promising alternatives due to their abundant reserves, low cost, and good catalytic performance under certain conditions. For instance, 10%Ni/r–SiO 2 –CIS illustrated good catalytic activity for nitrobenzene hydrogenation under the reaction condition of 150 °C and 1.0 MPa of H 2 , while Ni@NCQDs achieved high activity (100%) and selectivity (99.8%) for the reduction of p -chloronitrobenzene to p -chloroaniline. Ni/CeO 2 -CAS catalysts showed good catalytic performance for the reduction of various nitroarenes under 120 °C and 2.0 MPa of H 2 , and the Co/MA-800 nanocatalysts were active for the reductive amination of nitroarenes to obtain imines with high yields of product.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that a suitable combination of metal and support, the design of an efficient supported metal nanoparticle catalyst, and the use of metal–support interaction, can improve the dispersion of metal nanoparticles and effectively reduce the agglomeration of nanoparticles during the catalytic process. 28 Ma et al 16 successfully synthesized a supported nano-catalyst in which the non-noble metal Fe was supported on nitrogen-doped porous carbon derived from biomass, which was used to efficiently catalyze the oxidation of primary amine to imine with air as an oxidizing agent. Chen et al 17 reported a supported nano-catalyst with a mesoporous medium, homogeneous metal NPs and abundant oxygen vacancies for the synthesis of imines.…”
Section: Introductionmentioning
confidence: 99%